Characterization of the novel HLA‐DPA1*01:44 allele by sequencing‐based typing. (18th February 2021) - Cargou, Marine; Andreani, Marco; Giustiniani, Paola; Blouin, Laura; Visentin, Jonathan
Abstract : HLA‐DPA1*01:44 differs from DPA1*01:03:01:04 by one nucleotide substitution in codon 175 in exon 3.